Quasi‐White Light‐Emitting Devices Based on SiC Quantum Dots. Issue 8 (10th May 2018) - Chen, Xifang; Guo, Xiaoxiao; Wu, Wenhui; Fan, Jiyang
Abstract : White electroluminescence based on quantum dots (QDs) is usually realized by incorporating different types of QDs or QDs plus rare earth ion phosphors into a single device. Herein, we report quasi‐white electroluminescence in pure silicon carbide QDs‐based light‐emitting devices (LEDs). The carrier transport and recombination mechanisms are investigated through analyzing the current density versus bias curves and spatial distribution of energy levels. The carrier transport mechanism is dominated by quantum tunneling at low bias and direct injection at high bias, respectively. The quasi‐white electroluminescence arises from recombination of the injected electrons and holes in the SiC QDs in the devices. Abstract : Quasi‐white electroluminescence is realized in silicon carbide quantum dots (QDs)‐based light‐emitting devices. The carrier transport and recombination mechanisms are investigated through analysis of the bias dependence of the current density and the energy‐level diagram. The result shows that the carrier transport is dominated by quantum tunneling at low biases and direct injection at high biases. The quasi‐white electroluminescence arises from recombination of the injected carriers in the SiC QD layer.